Effectiveness of thin film application of imazalil fungicide on decay control of Tarocco orange fruit. (November 2016) - Altieri, Giuseppe; Genovese, Francesco; Tauriello, Antonella; Di Renzo, Giovanni C.; Strano, Maria C.; Romeo, Flora V.
Abstract : For oranges intended for European markets, it is strongly advisable to find preservation methods increasing shelf-life and favouring the reduction of use of chemical antifungal products, both for reasons of environmental sustainability and to reduce the risk to health. In this paper results related to imazalil fungicide treatment of oranges fruits are reported. The experiments were carried out by comparing the traditional dipping of fruit with an innovative pilot plant process, designated "thin film" (TF), which is designed to reduce fungicide/water mixture concentration. Two film thickness (1 and 3 mm) and two temperatures (20 and 45 °C) were investigated. The incidence of decay was <5% for all treatments during 60 d of cold storage and dipping at 45 °C showed a complete absence of decay during the cold storage. Imazalil residues inside fruits were <5 mg kg −1 using TF method while dipping produced residues >>5 mg kg −1 making the oranges unsuitable for the market. Therefore, TF treatment can be considered a useful method for maintaining high quality of citrus fruit and controlling green and blue mould both during cold storage and shelf-life period. A correlation was found between the overall decay incidence % and fungicide residue at time zero (adjusted R 2 of 0.98) and the fungicide destruction rate logarithmically depended on its initial dose. Highlights: Thin film treatment is an attractive alternative solution to dipping. It allows the control of the temperature of the active solution. Overall decay incidence and imazalil residue at time zero are strongly correlated. Imazalil destruction rate depends on imazalil initial concentration at time zero. Using small solution tank reduces the volume of waste water.